AN EFFECTIVE COMPUTATIONAL SCHEME FOR SOLVING VARIOUS MATHEMATICAL FRACTIONAL DIFFERENTIAL MODELS VIA NON-DYADIC HAAR WAVELETS: FRACTIONAL DIFFERENTIAL MODELS VIA NON-DYADIC HAAR WAVELETS - Kumar, Ratesh; Gupta, Jaya (Malaysian Journal of Science, 2024)
The Non-dyadic Haar wavelet (Haar scale-3) collocation approach is used in this article to generate numerical solutions of fractional differential equations. The nonlinear fractional ordinary differential equations are linearized using the Quasilinearisation technique. The Haar scale-3 wavelet approach works on transforming the set of differential calculations into a set of linear algebraic equations. The reliability of the numerical solution can be improved by raising the degree of resolution, and error analysis can be done. The numerical examples are solved to test the method’s simplicity and flexibility. The outcomes of numerical examples are compatible with the exact solution and provide better results than previous results existing in literature. This means that the procedure used here is consistent, reliable, and convenient to use.